Renewable Energy - Technologies and Applications 2021
DOI: 10.5772/intechopen.91340
|View full text |Cite
|
Sign up to set email alerts
|

Digestate: The Coproduct of Biofuel Production in a Circular Economy, and New Results for Cassava Peeling Residue Digestate

Abstract: Circular economic paradigm applies residue from one process as input material for another, fostering sustainable benefits for humanity. Anaerobic digestion (AD) is an attractive technology for biogas production in a circular economy. Digestate is the residual organic matter generated as coproduct of biogas. Because digestate is nutrient rich and largely stabilized, it has varied management options. Digestate is suitable for direct use as bio-fertilizer and is a good amendment material to improve soil physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…AD was probably recognized in a scientific sense about 392 years ago in 1630, when Jan Baptist van Helmont (1580-1644), observed that decomposing organic matter produced combustible gas; and during 1804-1808 John Dalton and Humphrey Davy established that the combustibility of the gas was due to the presence of methane [94,95]. Today, AD is carried out within artificial environments named digesters, which are designed to optimize the process [96][97][98]. The combustible gas is called biogas, and the watery sludge, digestate.…”
Section: Anaerobic Digestion (Ad) Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…AD was probably recognized in a scientific sense about 392 years ago in 1630, when Jan Baptist van Helmont (1580-1644), observed that decomposing organic matter produced combustible gas; and during 1804-1808 John Dalton and Humphrey Davy established that the combustibility of the gas was due to the presence of methane [94,95]. Today, AD is carried out within artificial environments named digesters, which are designed to optimize the process [96][97][98]. The combustible gas is called biogas, and the watery sludge, digestate.…”
Section: Anaerobic Digestion (Ad) Technologymentioning
confidence: 99%
“…Biogas is composed of methane (40-75%), carbon dioxide (25-40%), and trace contaminants (≈ 0.1-3%). Digestate is rich in plant growth macronutrients; with their quantities and micronutrients contents related to the quality of the feedstock [98,99]. Digestate attributes, AD's technical feasibilities, types of feedstocks utilized (virtually all organic matter), limitations, advantages, benefits, applications, and much more have been presented in the literature [83,96,98,[100][101][102].…”
Section: Anaerobic Digestion (Ad) Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of by-products, incineration facilities typically recycle the bottom ash to recover valuable metals, while the remaining ash can find use as construction materials, specifically aggregates [99]. In the case of anaerobic digestion, the primary by-product is digestate, a nutrient-rich material suitable for use as a fertilizer [100]. Gasification primarily results in ashes alongside the generated synthesis gas.…”
Section: Technical and Environmental Impact Of Wte Technologiesmentioning
confidence: 99%
“…The C that remains is usually highly stabilized, so C retention when applied to C-poor soils is likely to be at least the 10% assumed for other residues [80], equivalent to 5.8 × 10 4 to 4.7 × 10 6 t yr −1 . The retention and availability of nutrients (N and P) in the bioslurry is high, so bioslurry also acts as an excellent organic fertilizer [98][99][100], potentially replacing the production of fertilizers using fossil fuels.…”
Section: (C) Impacts On Soils Of Producing Crops For Energymentioning
confidence: 99%